THE NIGERIAN OIL RESOURCEAND SOVEREIGN WEALTH FUND: AN INTERROGATION - Joshua DANJUMA (International Studies Journal)
This article interrogates the Nigerian oil resource and Sovereign Wealth Fund and also investigates what Nigeria must do if it must escape the resource curse. Nigeria has actively engaged in oil exploration for about six decades and is the largest producer of oil resources on the African continent. During the oil boom of the 1970s, oil was the primary source of government revenue, amounting to about 80% of total income. The paper adopts content analysis of mainly secondary sources to examine the research problem at stake using the resource curse theory. Findings reveal poor political institutions, corruption and lack of accountability, weak executive control of oil resource governance with apparent inadequate checks and balances, and the resultant conflicts and clashes of interests, manipulations, and inflation of oil contracts with favouritism in allocating oil blocs to cronies.Therefore, this articleshades in a newlight by interrogating the Nigerian Sovereign Wealth Fund to ensure optimal benefits of oil wealth to all citizenry; it submits that measures must be adopted in building political institutions, reforming the Niger Delta Development Commission; diversification, building a welfare state, equitable distribution of oil wealth and the imposition of direct tax.